Fly, eagle, fly : An African tale - Gregorowski, Christopher (Margaret K. McElderry Books, 2008)
Fly, Eagle, Fly! is a charming and innovative adaptation of an African tale attributed to a Ghanaian, James Kwegyir Aggrey -- also known as Aggrey of Africa. How frequently we have thought that we were chickens destined to spend our lives limited to an earthly existence with limited horizons, whereas we are made for something far more noble. We are made for the sublime, the transcendent. We are not bound to this earth and a humdrum existence but are made for something truly glorious: We are not mere chickens but eagles destined to soar to sublime heights; we are made for freedom and laughter and goodness and love and eternity, despite all appearances to the contrary. We should be straining to become what we have it in us to become; to gaze at the rising sun and lift off and soar.